Influence of physical exercise on the operational performance of military police officers (Research, Society and Development, 2026)
Police activity is characterized by high physical and psychological demands. Exposure to stress, long working hours, and unpredictable situations can compromise the health and functional performance of these professionals. The general objective of this study was to analyze the relationship between regular physical exercise and the well-being of military police officers, seeking to understand its impacts on physical and mental health, as well as on the efficient execution of duties inherent to police work. The methodological design adopted was a bibliographic research of a descriptive nature, with a qualitative and quantitative approach. Studies involving police officers as participants were selected, investigating relationships between physical exercise, physical fitness, cardiometabolic health, occupational stress, and professional performance. The results indicate a high prevalence of sedentary behavior, overweight, obesity, hypertension, and metabolic syndrome among police officers, conditions associated with low levels of cardiorespiratory fitness and adverse occupational conditions. Conversely, regular and supervised physical exercise demonstrated a consistent association with reduced cardiovascular risk factors, improved body composition, decreased occupational stress, better quality-of-life indicators, and enhanced professional performance. A tendency toward a decline in physical conditioning over the course of the career was observed, particularly among officers with longer service time, reinforcing the need for permanent institutional health promotion programs. It is concluded that physical exercise represents a fundamental strategy for preventing cardiometabolic diseases, preserving mental health, and improving the operational performance of military police officers. Therefore, it should be considered an essential component of occupational health policies within police institutions.